2021
DOI: 10.31146/1682-8658-ecg-187-3-194-206
|View full text |Cite
|
Sign up to set email alerts
|

“Old” and “new” probiotics in the treatment of gastroenterological diseases in children and adults: how to increase effectiveness?

Abstract: The purpose of the review is to analyze the real benefits of the use of traditional probiotics and to highlight the issues of the possibility of creating and using new generation probiotics in the treatment of gastroenterological pathology. Questions of effectiveness of therapy with traditional probiotics of functional and organic diseases of the gastrointestinal tract in children and adults from the points of view of evidence-based medicine are analyzed, insufficient number of studies in children and frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Gonchar et al observed the incidence of acute respiratory infections in two groups in an orphanage: a group treated with daily E.faecium L3 suspension and a no-treatment group. The average number of acute respiratory infections (ARI) cases per child were 0.29 ± 0.13 in the group with enterococcal consumption and 0.73 ± 0.12 in the control group ( p < 0.05) [ 35 ].…”
Section: Probiotic Potential (Efficacy Of Enterococcal Strains)mentioning
confidence: 99%
“…Gonchar et al observed the incidence of acute respiratory infections in two groups in an orphanage: a group treated with daily E.faecium L3 suspension and a no-treatment group. The average number of acute respiratory infections (ARI) cases per child were 0.29 ± 0.13 in the group with enterococcal consumption and 0.73 ± 0.12 in the control group ( p < 0.05) [ 35 ].…”
Section: Probiotic Potential (Efficacy Of Enterococcal Strains)mentioning
confidence: 99%